2016
DOI: 10.1115/1.4033715
|View full text |Cite
|
Sign up to set email alerts
|

Performance Analysis of Capillary Compensated Hybrid Journal Bearing by Considering Combined Influence of Thermal Effects and Micropolar Lubricant

Abstract: The viscous dissipation of micropolar lubricant results in temperature increase of hole-entry hybrid journal bearing. Thermohydrostatic (THS) performance characteristics are computed by the concurrent solution of micropolar Reynolds, micropolar energy, and conduction equations. The results obtained numerically indicate that bearing is significantly affected by increase in temperature. Hence, it is essential to consider the thermal effects for bearing operating with micropolar lubricant to produce realistic bea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…The parameters listed in Table 1 have been taken from the previous published literature. 16,19,20 Lubricant film temperature ð…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The parameters listed in Table 1 have been taken from the previous published literature. 16,19,20 Lubricant film temperature ð…”
Section: Resultsmentioning
confidence: 99%
“…The complete solution procedure is shown in Figure 2. Block MPLR computes the nodal pressure values by using the system equations 19,20 and restrictor equation 4. Final equilibrium pressure values are transferred to block MENRGY for the computation of convergence in the pressure and temperature values is obtained (MITPR ¼ 1).…”
Section: Solution Schemementioning
confidence: 99%
See 1 more Smart Citation
“…Also, Bansal et al [22] highlighted elastic distortion effects on stability of micropolar lubricated hydrodynamic bearing and their results indicated that increase in flexibility causes decrease in stability. Various studies concerning the theory of micropolar lubricant and effects of micropolar parameters on performance and stability of journal bearings have also been reported in literature [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%
“…The obtained results demonstrated that: for highly loaded bearings operating at low speed, critical parameters are film thickness and maximum pressure; for high speed operating bearings submitted to a light load, the shaft being almost centered, heating becomes very significant and maximum temperature becomes the critical parameter. Pankaj Khatak and H.C. Garg [6] analyzed of the capillary compensated hybrid journal bearing by considering combined influence of thermal effects and a micropolar lubricant. The results obtained by numerically indicate that the bearing is significantly affected by increase in temperature.…”
Section: Introductionmentioning
confidence: 99%